Anaerobic oxidation of methane and associated microbiome in anoxic water of Northwestern Siberian lakes - Cabrol, Lea; Thalasso, Frederic; Gandois, Laure; Sepulveda-Jauregui, Armando; Martinez-Cruz, Karla; Teisserenc, Roman; Tananaev, Nikita; Tveit, Alexander; Svenning, Mette M.; Barret, Maialen (My University, 2020)
Arctic lakes emit methane (CH4) to the atmosphere. The magnitude of this flux could increase with permafrost thaw but might also be mitigated by microbial CH4 oxidation. Methane oxidation in oxic water has been extensively studied, while the contribution of anaerobic oxidation of methane (AOM) to CH4 mitigation is not fully understood. We have investigated four Northern Siberian stratified lakes in an area of discontinuous permafrost nearby Igarka, Russia. Analyses of CH4 concentrations in the water column demonstrated that 60 to 100% of upward diffusing CH4 was oxidized in the anoxic layers of the four lakes. A combination of pmoA and mcrA gene qPCR and 16S rRNA gene metabarcoding showed that the same taxa, all within Methylomonadaceae and including the predominant genus Methylobacter as well as Crenothrix, could be the major methane-oxidizing bacteria (MOB) in the anoxic water of the four lakes. Correlation between Methylomonadaceae and OTUs within Methylotenera, Geothrix and Geobacter genera indicated that AOM might occur in an interaction between MOB, denitrifiers and iron-cycling partners. We conclude that MOB within Methylomonadaceae could have a crucial impact on CH4 cycling in these Siberian Arctic lakes by mitigating the majority of produced CH4 before it leaves the anoxic zone. This finding emphasizes the importance of AOM by Methylomonadaceae and extends our knowledge about CH4 cycle in lakes, a crucial component of the global CH4 cycle.
Keywords: arctic; anaerobic oxidation of methane; methanotroph; methylomonadaceae; methylobacter; permafrost